Guidelines for designing middle-school transition using universal design for learning principles. (March 2019) - Chambers, Dianne; Coffey, Anne
Transition from primary (elementary) to secondary school can be both an exciting and a daunting prospect for young adolescents. Ensuring that students quickly settle into their new secondary school environment is the goal of transition programmes employed by schools. These programmes typically comprise a number of discrete and interrelated initiatives that often commence in the year prior to the move and continue during the initial months in the new school. These activities generally include specific initiatives for both the students and their parents. The needs of both groups are many and varied. It is critical that whatever transition events and strategies are planned, the needs of all students and parents are catered for. In this article the authors propose that the principles of Universal Design for Learning (UDL) may provide a useful basis for the development of transition programmes that address the needs of all participants. UDL is based on three principles which are: multiple means of engagement, multiple means of representation, and multiple means of action and expression. Examples outlining how these principles can be applied before, during and after transition are provided. The authors conclude with the proposition that research be conducted in a variety of cultural contexts and across countries to investigate whether transition programmes based on UDL principles better enable schools to meet the needs of all transitioning students and their parents.